Determination, characterization and modeling of aqueous biphasic systems composed of propylammonium-based ionic liquids and phosphate salts - Mussagy, Cassamo U. [UNESP]; Tabanez, Naiara L. [UNESP]; Farias, Fabiane O.; Kurnia, Kiki A.; Mafra, Marcos R.; Pereira, Jorge F.B. [UNESP] (Elsevier, 2020)
Ionic liquids (ILs)-based aqueous biphasic systems (ABS) are efficient platforms for the extraction and purification of biomolecules. To find more biocompatible ABS, propylammonium-based ILs, phosphate salts and water were mixed at three temperatures, evaluating the influence of IL and temperature on the liquid-liquid equilibria (LLE). The biphasic region increases with the increase of IL’ anionic/cationic chain and decreases with the increase of temperature. There is good agreement between the IL’ ability to form ABS and the hydrogen bonding interaction predicted by COSMO-RS. The subtle balance of hydrogen bonding between salt anion-water and IL anion-water governs the phase separation.
Keywords: Aqueous biphasic systems; COSMO-RS; Ionic liquids; Liquid-liquid extraction; NRTL; Phase diagrams